2011
DOI: 10.1016/j.bbmt.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Early CMV Viremia Is Associated with Impaired Viral Control following Nonmyeloablative Hematopoietic Cell Transplantation with a Total Lymphoid Irradiation and Antithymocyte Globulin Preparative Regimen

Abstract: The reconstitution of immune function after hematopoietic cell transplant (HCT) plays an important role in the control of viral infections. Both donor and recipient cytomegalovirus (CMV) serostatus has been shown to contribute to effective immune function; however, the influence of a nonmyeloablative preparative (NMA) regimen using total lymphoid irradiation (TLI) and antithymocyte globulin (ATG) on antiviral immune reconstitution has not yet been described. In 117 recipients of NMA HCT patients following ATG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…This is in line with a prior publication showing early CMV viremia due to impaired viral control in patients given grafts after TLI-ATG conditioning (23). Whether this is due to TLI/ATG conditioning or to the use of ATG itself remains to be determined.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is in line with a prior publication showing early CMV viremia due to impaired viral control in patients given grafts after TLI-ATG conditioning (23). Whether this is due to TLI/ATG conditioning or to the use of ATG itself remains to be determined.…”
Section: Discussionsupporting
confidence: 75%
“…In an effort at preventing GVHD, the Stanford group has developed another nonmyeloablative conditioning that combines total lymphoid irradiation (TLI, 8 Gy total dose) with anti-thymocyte globulin (ATG; 7.5 mg/kg thymoglobulin total dose; refs. [18][19][20][21][22][23]. This approach allowed sustained engraftment with a low incidence of GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…TLI regimens may have the appeal of offering improved protection from GVHD when compared with RIC regimens, while also limiting the volumes of normal tissue exposed when compared with any TBI regimen. Certainly, further study is warranted; increased odds of early CMV viremia have been demonstrated following TLI, 70 and other potential toxicities have yet to be explored. Having said this, TLI represents an appealing alternative to TBI in certain populations.…”
Section: Tli For Immunosuppression During Bmtmentioning
confidence: 99%
“…CMVseropositive patients were associated with early CMV reactivation in TLI-ATG. 33 CMV reactivation has been reported to be associated with a reduced risk of relapse, but only in patients with acute myeloid leukemia and not in those with lymphoma. 34,35 Unless the mechanism of CMV in enhancing GVL manifests differently in TLI-ATG, the enhanced GVL is likely to be related to the sex-mismatch.…”
mentioning
confidence: 99%